Community farm school approach for coconut seedlings/juveniles through collaborative social actions - Anithakumari, P.; Indhuja, S.; Shareefa, M. (Journal of Plantation Crops, 2023)
Three Grama Panchayats in Kerala's Alappuzha district undertook community-level participatory action research in 2019–2021. A total of 90 coconut farmers participated in the adoption of ICAR-CPCRI technology to produce West Coast Tall (WCT) coconut seedlings that are resistant/tolerant to the root (wilt) disease at the community level. Partners included extension agents, coconut producers' societies (CPS) and clusters, women self-help groups (WSHGs), and agricultural labor organizations. The characteristics of technologies that are suggested for adoption in root (wilt) disease-aﬀected tracts, such as the scientific management of young coconut trees and the production of high-quality seedlings through community nurseries, challenge the idea of adoption. There are a lot of variances in the homestead gardens' marginal holdings, including expertise, the use of technology, and access to advisory services. Government agencies provided the majority of the seedlings and extension advisory services, emphasizing the necessity for FPO-based or private extension in the coconut growing industry. The coconut farmers' understanding has significantly improved as a result of the participatory interventions for managing seedlings. The participatory demonstration and community farm school (CFS) strategy is discussed in the paper as a way for homesteads to manage juvenile coconuts while integrating new ideas and fostering cross and reciprocal learning. Refining the current extension approach requires integrating new knowledge about the characteristics of seedling growth, future economic performance, and social evaluation of choices of technological, individual, and skill-oriented interventions in risk-prone areas with debilitating root (wilt) disease.